Unveiling Research Trends in Good Governance - Fadhilah, Hasna Azmi; Rahmi, Haifa Zulfani (Indonesian Journal of Librarianship, 2023)
Background: The provision of public services by governmental entities embodies their dedication to enhancing societal well-being. The manifestation of superior and high-caliber public services serves as an inherent manifestation of effective governance. Nonetheless, there persists a deficiency in comprehensive comprehension regarding the intricacies of sound governance practices. Purpose: The objective of this study was to ascertain the prevailing research patterns within the domain of good governance. Method: To bridge this scholarly void, the investigation adopted a quantitative research paradigm incorporating a bibliometric framework to discern the trajectory of developments in the realm of good governance. Employing a purposive sampling technique, data collection centered on article documents pertaining to the specified timeframe of 2012 to 2022, encompassing works containing the designated keywords "good governance" and published in the English language. Result: The Scopus database showed 7772 scientific publications related to "good governance," which were narrowed down to 658 documents based on the above criteria. The number of publications increased significantly from 2018 to 2020, with the highest trends occurring in 2020 with 99 papers published. Furthermore, the 12837 keywords were grouped into six clusters, with 434 interconnected keywords. Conclusion: The Scopus database exhibited a total of 7772 scientific publications encompassing the subject of "good governance," from which a refined selection of 658 documents was extracted in accordance with the aforementioned criteria. Notably, there was a substantial surge in the number of publications observed between 2018 and 2020, with the apex of this upward trend manifesting in 2020, accounting for a noteworthy 99 papers published. Additionally, the extensive collection of 12837 keywords underwent a rigorous analysis resulting in the identification of six distinct clusters, comprised of 434 interconnected keywords. Keywords: Co-word Analysis; Bibliometric; Good Governance; Scopus